Evaluating the potential of testate amoebae as indicators of hydrological conditions in boreal forested peatlands. (August 2018) - Beaulne, Joannie; Magnan, Gabriel; Garneau, Michelle
Highlights: New knowledge on testate amoebae ecology in forested peatlands is presented. Testate amoebae can be used as environmental indicators in forested peatlands. A new transfer function for water table depth for forested peatlands is developed. Abstract: Testate amoebae are common proxies of past hydrological conditions in peatlands and are increasingly used as indicators of ecosystems ecological integrity. The ecology of these microorganisms is relatively well documented in non-forested ombrotrophic peatlands but there is a lack of data from forested peatlands, which are important ecosystems in boreal regions. This study provides the first testate amoebae modern training set ( n  = 72) from forested peatlands of the James Bay lowlands, eastern Canada. The relationships between testate amoeba communities and environmental variables (pH, water table depth, canopy openness, mineral particles concentration) were investigated using canonical correspondence analyses. Our data have shown that testate amoebae are sensitive environmental indicators in forested peatlands and can be used to reconstruct past hydrological conditions for these environments. A transfer function for water table depth (WTD) reconstructions was developed using weighted averaging models and was tested on a fossil testate amoebae record. In comparing forested and non-forested peatlands datasets we have shown that testate amoebae occupy similar ecological niches with respect to surface wetness in both ecosystems, but that their WTD optima is much higher (drier) in forested peatlands. The results show that the diversity and composition of testate amoeba assemblages do not vary significantly at the microform scale. This study provides new knowledge on testate amoebae ecology in forested peatlands that will improve further transfer function development in peatland ecosystems. This will allow a better evaluation of the responses of boreal forested peatlands to climate change, ecological disturbances and human activities.